Save the earth : an action handbook for kids - Miles, Betty; Davis, Nelle (New York : Distributed by Random House, 1991)
An overview of the environmental problems of land, atmosphere, water, energy, plants, animals, and people. Includes projects and a section on becoming an environmental activist.
Includes bibliographical references (p. 111-[112]) and index.
Keywords: Pollution -- Juvenile literature; Environmental protection -- Juvenile literature; Pollution -- Experiments -- Juvenile literature; Pollution; Environmental protection